Latina Girls' Sexual Education in the (New) Latinx Diaspora. Issue 2 (1st July 2019) - Clonan-Roy, Katherine
Abstract : In 1988, Michelle Fine explored the ways in which damaging patriarchal discourses about sexuality affect adolescent girls, and hinder their development of sexual desire, subjectivities, and responsibility. In this article, I emphasize the durability and pliability of those discourses three decades later. While they have endured, they shift depending on context and the intersections of girls' race, class, and gender identities. Calling on ethnographic research, I analyze the intersectional nuances in these sexual lessons for Latina girls in one (New) Latinx Diaspora town.